Determinación de variables morfométricas en glándulas endometriales en los días 30 y 70 de la gestación en porcinos - Fiorimanti, M.R. (2022)
Morphological variables, number, lumen area and cell height of the endometrial glands of the pregnant sow were determined at an early stage of 30 days and in a late average at day 70. Placental samples of 30 and 70 days of gestation were obtained from slaughterhouses from Río Cuarto, (Córdoba, Argentina). Part of the placentas were processed using the conventional optical microscopy technique and destined for digital analysis of glandular morphometry. Another part was processed by the conventional electron microscopy technique for the MOAR technique. A significantly higher number of endometrial glands was detected on day 30 of gestation compared to day 70. The glandular lumen area was significantly greater on day 70 compared to day 30 of gestation. Cell height was significantly higher on day 30 of gestation. The MOAR technique allowed visualizing the glandular epithelium in greater detail and differentiating ciliated from secretory cells. In early gestation, glandular growth is active, with numerous glands and moderate secretory activity. In late mid-gestation, the endometrial glands would not increase in number, but in secretory activity, accompanying the increasing metabolic demands of the developing fetus.